COMPENSATION OF EDUCATIONAL DEFICIENCIES IN CHILDREN STAYING IN FOSTER CARE IN BIALAPODLASKAPOVIAT - Ruszkowska, Marzena Urszula; Wołosiuk, Beata; Sobczuk, Sebastian; Zdunkiewicz, Piotr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The material for the article was created as part of the project "Education, levelling developmental and educational deficits of charges of family-run children’s houses and care and educational institutions (based on the example of Biała Podlaska poviat)" implemented by the Department of Pedagogy of Higher State School in Biała Podlaska. Two methods: diagnostic survey and study of individual cases were used in the research, using proprietary questionnaires for charges, interview questionnaires with educators of care and educational centres and family facilities, an observation sheet and talks with coordinators and directors of the examined institutions. The research was carried out in Biała Podlaska poviat in three care and educational centres and three family-run children's homes. The subject of the article was to implement the educational needs of foster care children, including the issue of levelling educational gaps. The aim of the study was to determine whether educational deficiencies are noticeable there, what is the compensation of these deficiencies in family and institutional settings, if any of these forms is more favourable, what factors affect the proper satisfaction of educational needs? The analysis of the results made it possible to conclude that educational needs are realized in both care and educational centres and in family-run children’s homes, the beneficiaries of both forms exhibit numerous educational deficiencies conditioned by previous educational negligence. Compensation of educational deficiencies is more beneficial in family care. The basic forms of compensating for gaps include: tutoring, compensatory classes, individual caregiver work with a child, colleague self-help, voluntary activities.